2013
DOI: 10.4103/0972-2327.120455
|View full text |Cite
|
Sign up to set email alerts
|

Spinocerebellar ataxia type 7: Report of an Indian family

Abstract: Spinocerebellar ataxia type 7 (SCA7) is a form of autosomal dominant cerebellar ataxia which is associated with pigmentary retinal degeneration. It is known for its world-wide rarity except in the Scandinavian countries. It is very rarely reported from India and the neighbouring Asian countries. The present report describes the neurogenetic findings of a family of SCA7, from the northern part of Karnataka in South India. It documents the wide intrafamilial phenotypic variability, which could be correlated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
4
1
Order By: Relevance
“…Ahn et al described a bull's eye macular configuration with FA in one patient [32]. This was not the case for a patient with foveal thinning at SDOCT, described by Park et al, where fundus examination, FA, and FAF were normal [29]. In examining patient 3 in our case series, we reported NIR images that highlighted areas of granular retinal appearance that were not visible with CFP and showed hyperreflective foveae in both eyes.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…Ahn et al described a bull's eye macular configuration with FA in one patient [32]. This was not the case for a patient with foveal thinning at SDOCT, described by Park et al, where fundus examination, FA, and FAF were normal [29]. In examining patient 3 in our case series, we reported NIR images that highlighted areas of granular retinal appearance that were not visible with CFP and showed hyperreflective foveae in both eyes.…”
Section: Discussioncontrasting
confidence: 48%
“…In 2002, Aleman et al were among the first to present the SDOCT characteristics of three patients with SCA7, describing foveal and parafoveal thinning with an abnormally low reflectivity splitting of the outer retina-choroidal complex [22]. Other authors, including Park et al, later confirmed these findings, describing foveal thinning with focal disruption of the ellipsoid zone and central loss of the outer segment-RPE interdigitation zone [29]. In 2021, Zou et al described the presence of hyperreflective dots as a common finding in outer retinal and choroidal vessel layers.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Wali et al, 2013* [79] Belgaum region of Northern Karnataka, Southern India [81] Adukkamparai village in Vellore, India 100 37 --------Faruq et al, 2015 [50] Haryana (a state in Northern India)…”
Section: Discussionmentioning
confidence: 99%
“…Voxel‐based morphometry, diffusion tensor imaging, and magnetic resonance spectroscopy show promise in detecting early changes in other ataxias, and they will likely be instructive for SCA7 as well. It remains to be shown whether early findings on imaging correlate with preclinical findings such as hyperreflexia, abnormal ERG, or perhaps ocular coherence tomography (eg, Wali) to detect the transition from phenotypically normal individuals, to those who are clinically normal but physiologically abnormal. Furthermore, it remains to be seen how these potential biomarkers will further refine the rating scales for ataxia.…”
Section: Discussionmentioning
confidence: 99%